Preparation of cyclodextrin-based porous polymeric membrane by bulk polymerization of ethyl acrylate in the presence of cyclodextrin. (26th August 2019) - Kobayashi, Yuichiro; Nakamitsu, Yukie; Zheng, Yongtai; Takashima, Yoshinori; Yamaguchi, Hiroyasu; Harada, Akira
Abstract: We disclose an efficient synthesis to prepare polymeric membranes containing cyclodextrins (CDs). Bulk polymerization of ethyl acrylate containing peracetylated γ-CD (PAcγCD) yields a porous polymeric membrane containing CDs [CD membrane (BP)]. Krypton adsorption measurements reveal that the CD membrane (BP) has a porous structure. The specific surface area of the CD membrane (BP) is 10 times higher than that of a CD-based polymeric membrane prepared via solution casting using a solution containing poly(ethyl acrylate) and PAcγCD. Due to the large specific surface area of the CD membrane (BP) and the molecular recognition of CD, the capabilities and selectivity of CD membrane (BP) to separate bisphenol A as an environmental pollutant from water are demonstrated. Graphical abstract: Image 1 Highlights: A cyclodextrin (CD)-derived polymeric membrane is obtained by bulk polymerization of radical monomer containing CD. . The CD-derived polymeric membrane has a porous structure. . The CD-derived polymeric membrane shows a high separation capacity for environmental pollutants. . The CD-derived polymeric membrane exhibit a selective separation ability based on the molecular recognition of CD. .